Comparison of three different staining methods for the morphometric characterization of Alpaca (Vicugna pacos) sperm, using ISAS® CASA-Morph system - Cucho, Hernán; López, Yolvi; Caldeira, Carina; Valverde-Abarca, Anthony; Ordóñez, César; Soler, Carles (Nova Biologica Reperta, 2019)
Sperm morphometry is a part of the semen analysis based on CASA technology and has shown a big role in the prediction of male fertility. This analysis implies the use of stain techniques, although it has been shown that staining can make dramatic changes in the cell morphometry in different species. The aim of the present work was to evaluate the differences in sperm morphometry in Alpaca, introduced by the use of different stain techniques. Single ejaculates from five adult alpacas were used. Samples were recovered by deferent duct deviation surgery technique. Three stain techniques (i.e. Hemacolor, Harri’s Henatoxylin and Diff-Quik) were evaluated. Morphometric analysis was done using ISAS® v1 CASA -Morph system, at 100x bright field objective magnification and a digital video camera with a final resolution of 0.08 µm/pixel. Almost 200 randomly selected cells were automatically analysed per sample and stain technique, considering several sperm-head and midpiece parameters regarding size and shape. Almost all of the parameters showed different levels of difference among the employedtechniques. In general, the largest cell heads were the ones stained with Harri’s Hematoxylin and the smallest ones were the ones stained with Diff-Quik. The discriminant parameters used to differentiate between animals better were the head width, area and acrosome percentage. In conclusion, like in other species, alpaca sperm morphometry results were found to be sensitive to the applied stain technique. This implies the necessity of referring clearly the stain technique used in each case to perform comparisons between different works on the same species. None of the employed techniques was superior to the others. In addition, the method used to obtain the samples showed its usefulness and simplicity for repeated samplings.
Nova Biologica Reperta, vol. 6, no.3 (2019):284-291
Keywords: Alpaca; Semen -- Análisis; Diff-Quik -- Técnicas de laboratorio; Citodiagnóstico veterinario; Casa Programa para computador